Inheritance by estimation in Islamic jurisprudence and law - Ali Shahab Ahmed; Qusay Hussein Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Inheritance in estimation is a chapter confirmed from the time it is proven, where the reasons for inheritance are available, but the heirs' shares are not clear and specific unless they are based on an order to be made. It guarantees the right of such heirs as the missing, the captive the burnt and others. This branch in inheritance is a precise science that depends on stages. The fetus is given the best chance of inheritance by assessing its male or female according to his real existence in his mother's womb in a specific period, his birth alive. However, the heirs' shares change depending on the type of fetus after birth. Epicene is given the lowest levels and, as being problematic, undergoes certain procedures and methods to determine its male-hood from its femininity. Then, the heirs' share also changes in case of epicene's procedures. The missing person shall retain his share of the estate until his life is known from his death or the judge shall decide his death after the legal period has passed. Accordingly, his share of the from the estate shall be distributed to those who deserve it. The prisoner's share remains suspended until he his death is states. For the plunderers, the destitute, the burnt and others, there are certain legislations that determine their inheritance among themselves by knowing the precedence of death, so that they do not inherit without knowing their precedence. The Iraqi law did not address any of the persons who are estimated to inherit, except for the wife of the missing in the Iraqi personal status law and the ruling of the death of the lost and the distribution of his legacy in the law for the care of Iraqi underage.